Hikayat Indarjaya sebagai Suplemen Materi Cerita Fantasi Kelas VII Kurikulum Merdeka: Analisis Ciri Cerita Fantasi dan Implementasi Pembelajarannya (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
This study aims to determine the suitability of Hikayat Indarjaya as a supplement to fantasy story material and describe the implementation of Hikayat Indarjaya in teaching fantasy stories for class VII SMP/MTs. The method used in this research was descriptive qualitative research. The data source was Hikayat Indarjaya, the result of a study published in 1995. The instruments used to collect data were data codification guidelines, data collection rubrics, and data analysis rubrics. The results of this study state that Hikayat Indajaya corresponds to the characteristics of fantasy stories, namely (1) there are magical, mysterious, or strange events, (2) open story ideas, (3) using various settings in places and times, (4) has a unique character, (5) fictitious, and (6) the use of language. Students can be given this hikayat material to strengthen understanding and be used as a supplement to fantasy story text material either through pupuh or script summaries.